2007
DOI: 10.1007/s00442-007-0795-y
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific density determines the magnitude and character of predator-induced phenotype

Abstract: The benefits in survival gained from predator-induced phenotypes often come at a cost to other components of fitness. Therefore, the level of expression of an induced phenotype should mirror the level of risk in the environment. When a predator exhibits a saturating functional response the risk of mortality to a given prey decreases as prey density increases. Therefore, for a given predator threat, investment in defense should be lower in prey at high density relative to those at low density. In this study, I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 59 publications
5
48
1
Order By: Relevance
“…Such a mechanism was supported previously by Van Buskirk et al. (2011) and McCoy (2007). Van Buskirk et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism was supported previously by Van Buskirk et al. (2011) and McCoy (2007). Van Buskirk et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2011) reported that Rana temporaria tadpoles respond behaviorally to per capita predation risks imposed by Aeshna cyanea dragonfly larvae and that these responses decreased as prey conspecific density increased. McCoy (2007), in turn, reported that morphological predator‐induced changes in Hyla chrysoscelis were reduced in response to increased conspecific density when subjected to predation risk imposed by the Lethocerus americanus giant water bug.…”
Section: Discussionmentioning
confidence: 99%
“…This approach provides an advantage over previous studies of inducible defences in that it allows one to distinguish between morphological differences that are a by-product of behaviour and growth versus a direct response to risk cues. It also aids in the interpretation of studies of phenotypic plasticity where morphological relationships can change with body size, and body size often varies among treatments (McCoy 2007). For example, because of differences in growth, high-food and crab-exposed snails differed in final size, making differences in shell mass and shell deposition between high-food and crab treatments difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…To date, predator-inducible morphological defenses in aquatic organisms have served as excellent model systems for testing predictions about the evolution and maintenance of phenotypic plasticity (Ghalambor et al 2007). However, it has been shown that prey population density (i.e., conspecific density) and its effects on the assessment of predation risk by the prey can be very important for determining the extent to which prey express anti-predator defenses (Roberts 1996, McCoy 2007, Van Buskirk et al 2011. Peacor (2003) has noted that prey need to estimate their own population density to better assess risk, especially if the prey detects the presence of a predator through predation cues.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies that have evaluated the effects of conspecific density on predator-induced responses have aimed to test the role of prey resource competition in limiting phenotypic plasticity (Tejedo andReques 1994, Davenport andChalcraft 2014). Prey should be unable to express predator-induced phenotypes because resources are scarce and impose a physiological limitation on morphological development, a rationale that neglects the principle that conspecific density modifies the prey's perceived risk (McCoy 2007, Van Buskirk et al 2011). In addition, historically, many of the studies addressing the role of predator-induced defenses have examined the effects of conspecific density on a single plastic trait (e.g., activity levels) (Relyea 2001).…”
Section: Introductionmentioning
confidence: 99%